The significance of the nominal and the verbal sentence in the book (Al-Siraj Al-Munir fi Bayan Nukat Al-Tafsir) by Sheikh Habib Al-Kadhimi - Daif Kased, Assist. Lect . Ahmed (Basra studies journal, 2025)
The importance of the sentence is due to its importance in realizing the meanings of words, and carrying aesthetic values ​​and expressive secrets. The nominal sentence indicates the permanence that it derives from nouns only, because the noun is the basis upon which the nominal sentence is built, so it indicates permanence. As for verbal sentences, they indicate renewal that depending on their verbs. Therefore, it indicates occurrence and renewal, so it depends on the verb that indicates the action, and acquires meaning from it. The research was divided into a theoretical entrance in which the researcher explained the concept of the sentence and its meaning according to what linguists, rhetoricians, and interpreters dealt with in understanding the Qur’anic texts. Then the researcher dealt with the meaning of the sentence and its purposes. After that, the meaning of the sentence was explained and the types of sentences and their meaning were stopped, all of that according to the semantic stops that Sheikh Habib Al-Kadhimi was concerned with in Al-Siraj Al-Munir in explaining the points of interpretation. All of that was preceded by an introduction that included talking about the importance of the topic and the reasons for choosing it, followed by a conclusion that included the most important results that the research reached, then there was a list of sources that the researcher relied on.